Investigations on Electromagnetic Interference Shielding behaviour of Graphene based Polypyrrole nanocomposites - Gill, Nisha (My University, 2021)
The electromagnetic interference (EMI) shielding of different electronic gadgets have attracted a lot of attention due to its various applications in industries, defence and electronic communication. The electromagnetic interference present in theenvironment through different possible ways may also affect the human health. Therefore, essentiality of EMI shielding has also been considered for checking the electromagnetic pollution. In order to attenuate the electromagnetic radiation, a shielding material is required. The electromagnetic shielding is done bythree ways i.e. reflection, absorption and multiple reflection. The ability of a material to attenuate the intensity of electromagnetic wave is given by shielding effectiveness (SE). The total SEgreater than 30 dB corresponds to 99.9 % attenuation of microwave radiation and is useful for various defence, military applications. Metals, ceramics and various other composites have been investigated in the quest of vary good EMI shielding materials. These composites have several advantages such as low cost, easy to process, free from corrosion etc. Thereare several frequency bands of microwave defined by Radio Society of Great Britain (RSGB) such as L, C, X, Ku band etc., which are important for different specific purposes ranging from defence to atmospheric science, microwave communication to checking of environmental pollution etc. The X-frequency band of microwave (8.2-12.4 GHz) is useful for many commercial and military application such as Dopplerweather radar, TV transmissionetc. These applications require high shielding due to absorbing along with decreased shielding due to reflection. The materials having high dielectric permittivity and high magnetic permeability may having very good microwave absorbing properties by virtue of presence of electric and magnetic dipoles. When the electromagnetic wave interact with these dipoles, the electromagnetic field of electromagnetic wave may lead/lag with respect to the internal field of these dipoles which causes the attenuation of electromagnetic wave.Therefore, the nanocomposite materials consisting of conducting polymer and carbon based nanofillers along with ferrite nanoparticles could be an alternative choice of EMI shielding material.These materials may exhibit very good microwave absorbing behaviour in the X-band. Therefore, investigations on electromagnetic shielding behaviour of graphene based polypyrrole nanocomposites have been carried out. The iibasic, analysis and outcome of these investigations are compiled in five chapters in the present thesis.The first chapter discuss the fundamentals of electromagnetic theory and its relevance to the electromagnetic interference (EMI) shielding phenomena. A brief review of different class of EMI shielding materials (viz.metals, ceramic,ceramic based composites and polymer based composite materials) arealso presented. The role of the interfacial modification, dielectric and magnetic losses, mechanical strength have significant effect on the shielding effectiveness behaviour of the polymer based composite. These studies are helpful in deciding the aim of thesis, which is mentioned in the last section of this chapter. The second chapter describes the various methods and experimental techniques used for synthesis and characterization of graphene based polypyrrole nanocomposites. Synthesis of cobalt ferrite nanoparticles and graphene nanosheets have been done by hydrothermal method and liquid phase exfoliation method respectively. Synthesis of the polypyrrole based nanocompositesis carried out by in-situchemical oxidative polymerization technique. Structural and morphological characterization have been done by X-ray diffraction (XRD), transmission electron microscopy (TEM), Fourier transform infrared (FTIR) and Raman spectroscopy. The magnetic measurement has been studied by vibrating sample magnetometer (VSM). The brief description of all these characterization techniques are also included in this chapter. Electrical studies has been done by current-voltage measurements at room temperature. The electromagnetic shielding effectiveness, dielectric and magnetic parameters in X-band (8.2-12.4 GHz) have been measured by vector network analyzer (VNA). The various parameters associated with EMI shielding such as dielectric permittivity, magnetic permeability, ac conductivity and skin depth are explained in the last portion of this chapter. Third chapter discusses the electromagnetic shielding behaviour of polypyrrole-graphene nanocomposite in X-band. The polypyrrole-graphene nanocomposites have been synthesized by in-situchemical oxidative polymerization method. X-ray diffraction, transmission electron microscopy, Fourier transform infrared and Raman spectra have been carried out for structural and morphological studies. The electromagnetic shielding and dielectric relaxation behaviour of nanocomposite have been investigated in X-band (8.2-12.4 GHz) of microwave. Microwave absorption and reflection behaviour have been iiianalyzed and, correlated with the dielectric permittivity, skin depth, ac conductivity and attenuation constant. The qualitative explanation of mechanism of observed shielding effectiveness by various processes is also given. This chapter is concluded with important outcomes of experimental results.Fourth chapter deals with the investigation on the effect of inclusion of graphene nanosheets on EMI shielding behaviour of polypyrrole-cobalt ferrite-graphene nanocomposite in X-band. Polypyrrole-cobalt ferrite-graphene nanocomposites have been synthesized by in-situchemical oxidative polymerization. The formation of nanocomposites with different loading percentage of graphene have been confirmed by X-ray diffraction, Fourier transform infrared and transmission electron microscopy. The effect of graphene loading in nanocomposite on shielding effectiveness, dielectric permittivity, magnetic permeability, ac conductivity and skin depth has been studied in X-band (8.2-12.4 GHz). Mechanism of shielding effectiveness by various processes i.e. reflection, absorption, multiple reflections etc. is also illustrated qualitatively. This chapter is concluded with important outcomes of experimental results. The summary and the conclusions drawn from the study of investigation of electromagnetic interference shielding ofgraphene based polypyrrole nanocomposites has been given in the fifth chapter. The future scope for further investigation has also been suggested.
Keywords: EMI shielding; Polymer-graphene nanocomposites; microwave dielectric behaviour